THE EFFECT OF FREE CASH FLOW, LEVERAGE AND PROFITABILITY ON DIVIDEND POLICY THROUGH CASH HOLDING ON PHARMACEUTICAL COMPANIES LISTED ON THE EXCHANGE INDONESIA EFFECT - Yulizartika, Yulizartika; Satriawan, Bambang; Robin, Robin; Khaddafi, Muammar; Wibisono, Chablullah (CV. Radja Publika, 2022)
This study aims to analyze Free Cash Flow, Leverage, and Profitability that affect Dividend Policy with Cash Holding as an intervening variable in Pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017-2021. The population in this study amounted to 12 companies. The sample selection method used purposive sampling technique, so the number of samples used was 8 companies. The number of observations used is 40 observations. The type of data used is secondary data with data analysis techniques used, namely panel data regression analysis with multiple linear regression tests and path analysis using Eviews software. The results showed that Free Cash Flow had a positive and insignificant effect on Dividend Policy, Leverage, Profitability and Cash Holding have no significant negative effect on Dividend Policy. Free Cash Flow and Profitability have a significant positive effect on Cash Ownership. Leverage has a negative and insignificant effect on Cash Holding. Cash Holding can only mediate Leverage on Dividend Policy